2014
DOI: 10.4103/0253-7176.135394
|View full text |Cite
|
Sign up to set email alerts
|

Functional Convergence Spasm

Abstract: Convergence spasm (CS) means intermittent episodes of convergence, miosis and accommodation with disconjugate gaze mimicking abducens palsy. The organic causes range from metabolic to host of neurological and ophthalmic diseases that we describe. It was first described as a presentation of psychogenic disorders by von Graefe as early as in 1856. Nonetheless, patients exhibiting this sign are often subjected to plethora of unnecessary, sophisticated and invasive diagnostic procedures. Such functional cases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…In our case, no organic cause was found for the spasm, which was intermittent for years. Psychogenic therapy [ 6 , 9 ] and pharmacological treatment with cycloplegic eye drops [ 7 ] are noninvasive methods which led to successful resolution of accommodative spasm in isolated cases, but they are often temporary and not long lasting or curing the disease [ 3 ]. Sertraline is a selective serotonin reuptake inhibitor which is used as an anxiolytic and for emotional distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, no organic cause was found for the spasm, which was intermittent for years. Psychogenic therapy [ 6 , 9 ] and pharmacological treatment with cycloplegic eye drops [ 7 ] are noninvasive methods which led to successful resolution of accommodative spasm in isolated cases, but they are often temporary and not long lasting or curing the disease [ 3 ]. Sertraline is a selective serotonin reuptake inhibitor which is used as an anxiolytic and for emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Possible organic causes are of neurologic cerebral origin, attempts to overcome vertical gaze palsy, or endocrine metabolic dysfunctions [ 4 , 5 ]. Treatment depends on the possible etiology, but often no organic cause can be found [ 6 ]. Symptomatic treatment exists in pharmacological cycloplegia [ 7 ], with possible persistence of the spasm after cessation of the therapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Convergence spasm (CS) consists of episodes of lens accommodation with ocular convergence usually causing diplopia, evoked mainly by horizontal ocular pursuit. 50 , 51 In a study with blinded raters, CS was observed in 69% of patients with PMDs, but in only 36% and 33% of patients with non-psychogenic movement disorders and healthy controls, respectively (p = 0.049), with good agreement between raters. 50 While CS may be due to brainstem pathology, it is often associated with other psychogenic manifestations leading to inappropriate workup.…”
Section: Methodsmentioning
confidence: 98%
“…The timing of resolution also coincided with fingolimod and fingolimod phosphate pharmacokinetics with an established half-life of 6À9 days. 3 For a typical BRVO, retinal hemorrhages and intraretinal edema usually take many months to resolve.…”
Section: Branch Retinal Vein Occlusion Associated With Fingolimod Treatment For Multiple Sclerosismentioning
confidence: 99%
“…Convergence spasm can be nonorganic, but one must exclude organic pathology such as encephalitis, aromatic L-amino acid decarboxylase deficiency, tabes dorsalis, thyroid disease, or multiple sclerosis. 3 Nonorganic causes include conversion disorder, pseudoseizures, and other neuropsychiatric conditions. Tilikete et al reported cases of 2 patients with anti-GAD65 antibody syndrome both of whom had cerebellar ataxia with nystagmus.…”
mentioning
confidence: 99%